The Role of the Ustadz in Improving the Understanding of Fiqh of Students Class 6 at Ibtidaiyyah Islamic Darul Falah - Bustomi, Ahmad; Ehwanudin, Ehwanudin; Irhamudin, Irhamudin (International Journal on Advanced Science, Education, and Religion, 2025)
The Madrasahs have a strategic role in increasing students' religious understanding, especially in the field of Fiqh as a guide to Islamic law in everyday life. This research aims to analyze the role of Ustadz in improving the understanding of Islamic Fiqh for Class 6 Ibtidaiyyah students at the Darul Falah Madrasah, which is located in the Darul Ulum Islamic Boarding School environment, Seputih Banyak, Central Lampung. This research uses a qualitative approach with the phenomenological method, involving observation, in-depth interviews, and document analysis as data collection techniques. The research results show that Madrasas as non-formal educational institutions play a role in providing a systematic Fiqh curriculum, while Ustadz play a role as teachers, educators and guides in the learning process. The methods used in learning Fiqh include lectures, discussions, demonstrations, questions and answers, and memorization. However, there are several challenges in learning Fiqh in Madrasas, such as limited learning resources, variations in the level of understanding of students, and different learning motivations. To overcome these challenges, Ustadz applies practice-based learning strategies, contextual approaches, uses learning media, and strengthens the character of students through direct guidance. This research confirms that the effectiveness of Fiqh learning in Madrasahs is very dependent on the active role of the Ustadz and the learning strategies implemented. It is hoped that this study can become a reference in improving the quality of Fiqh learning in Madrasas as part of the Islamic education system.